Pengembangan Media Pembelajaran Berbasis Android Menggunakan Ispring Suite Pada Materi Momentum dan Impuls - Nila Mutia; Ahmad Jahrudin; Dandan Luhur Saraswati (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2022)
This study aims to develop learning media in the form of Applications on Momentum and Impulse Materials using the Ispring Suite. In this case, the researcher develops learning media in the field of education that integrates with the development of information and communication technology, namely by utilizing cell phones which basically almost 99% of students already have. The learning media developed is an application called Pemodim. The research method used in this research is the research and development method with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation) which is a learning design model based on an interactive systems approach. This mod was created using PowerPoint and then Published using the Ispring Suite Software into HTML, after that it was converted into an Android application form with the help of Website 2 APK Builder Software. This Pemodim learning media is equipped with material applications in the form of text and also images and learning videos so that it becomes a device solution in supporting education, especially Physics. This android-based learning media is also said to be feasible to use based on validation from media experts, material experts, linguists, and education practitioners. The average total score of 88% for the media expert validation assessment, the average total score of 90% for the material expert validation assessment, the average total score of 84% for the linguist validation assessment, and the average total score of 89 % for the validation assessment of education practitioners, each of which results fall into the "Very Eligible" criteria. In addition, a limited test has been carried out on 7 students getting an average score of 87% and the test was extended to 20 students getting an average score of 90% so the total is 27 students in the very good category.